2002
DOI: 10.1017/s0033291702005354
|View full text |Cite
|
Sign up to set email alerts
|

Long-term adjustment in burn victims: a matched-control study

Abstract: Severely burned patients adjust relatively well, although some develop clinically-significant psychological disturbances such as somatization and phobic anxiety. Burn patients experiencing abnormal sensations in their healed wounds (i.e. symptomatic patients) do not suffer from maladjustment to a greater extent than their asymptomatic counterparts, although more symptomatic patients experience somatization and obsessive-compulsive behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 29 publications
0
21
1
1
Order By: Relevance
“…Adult burn survivors evaluated roughly 5 years postburn, relative to a matched unburned, healthy control group, reported a quality of life that was comparable with controls. 18 However, approximately 25% of burn patients present clinically significant psychological disturbances compared with only 12% of control participants. Burn survivors experiencing abnormal sensations in their healed wounds, relative to burn patients with normal sensation, report more somatizing and obsessive-compulsive behaviors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Adult burn survivors evaluated roughly 5 years postburn, relative to a matched unburned, healthy control group, reported a quality of life that was comparable with controls. 18 However, approximately 25% of burn patients present clinically significant psychological disturbances compared with only 12% of control participants. Burn survivors experiencing abnormal sensations in their healed wounds, relative to burn patients with normal sensation, report more somatizing and obsessive-compulsive behaviors.…”
mentioning
confidence: 99%
“…However, many previous studies have been limited by cross-sectional designs, 13,16,18 without prospective assessment, 17,18 limited geographic distribution, 13,16,18 lack of preinjury measures of quality of life, 16 -18 small sample size with short-term followup, 6 -8 and lack of reference to normative data. 16,17 The best (well-designed) study to date reported only on one dimension of quality of life (ie, life satisfaction), 14 leaving unanswered questions regarding how other dimensions (eg, health and function) are affected by a major burn injury.…”
mentioning
confidence: 99%
“…These provocative findings came from a number of case studies of patients who developed OCD after combat exposure, sexual assault, personal violence, and serious road traffic accidents [1][2][3][4], from phenomenological descriptions [5][6][7][8][9][10] and neuroimaging studies [11,12] showing important similarities between OCD and post-traumatic stress disorder (PTSD), and from epidemiologic findings suggesting the presence of a significant link between victimization and the development of OCD in the general population [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Several significant findings support the existence an important phenomenological overlap between OCD and PTSD [5][6][7][8][9][10]. For example, while both OCD obsessive imagery and PTSD flashbacks may be characterized by their unpleasant, vivid, repetitive and intrusive qualities [7], compulsive rituals and severe avoidant behaviors may provide and increased sense of safety to patients suffering from both disorders [5].…”
Section: Introductionmentioning
confidence: 99%
“…in pediatric burn survivors is estimated to be between 25% and 30% (Meyer et al 1995;Altier et al 2002). Many of these children develop acute stress disorder (ASD) (Stoddard 1990), which was first defined as a separate entity from posttraumatic stress disorder (PTSD) in the Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV) (American Psychiatric Association 1994).…”
Section: Introduction T He Prevalence Of Psychological Sequelaementioning
confidence: 99%